People and places: social and physical aspects of life experienced by persons with disability after their relocation to community - Gevorgianienė, Violeta; Šumskienė, Eglė; Mataitytė-Diržienė, Jurga; Genienė, Rasa (Special Education, 2021)
The article discusses the issues related to the integration of people with intellectual disabilities and mental disorders in the community after they have relocated to a community group home. The ecological mapping approach reveals and compares aspects of the physical and social participation of people with disabilities and other community members.